The potential of cellulose-degrading fungi at various peat maturities in Teluk Bakung Peat Area, Kubu Raya District, Indonesia - Siti Khotimah; Suharjono Suharjono; Tri Ardyati; Yulia Nuraini (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Khotimah S, Suharjono, Ardyati T, Nuraini Y. 2021. The potential of cellulose-degrading fungi at various peat maturities in Teluk Bakung Peat Area, Kubu Raya District, Indonesia. Biodiversitas 22: 1981-1990. Fungi play important roles in degrading cellulose in the maturation process of peat. This study aimed to evaluate the potential of cellulose-degrading fungi at various peat maturities in the forest. Peat soil samples were collected from Teluk Bakung Village, Kubu Raya District, West Kalimantan using a random sampling method. Peat soil samples were obtained at six sampling sites in forests and palm oil plantations. The fungi were cultured by the pour plate method on 1% CMC media. The cellulose-degrading fungi were determined based on a clear zone formation around the colony in CMC agar media. The cellulolytic fungal population in the fibric, hemic, and sapric peats of the secondary forest were 3.2 × 103, 4.6 × 103, and 5.6 × 103 CFU/g, respectively, whereas at fibric, hemic, and sapric of the shrubs were 5.6 x 104, 3.9 × 105 and 4.7 × 104 CFU/g, respectively. Among the 25 cellulolytic fungal isolates, 5 isolates (HS1.5, HS3.4.1, HB2.2, SS2.4.1, and SB2.5.1) showed high average clear zone diameter (21-28 mm). The HS3.4.1 and HS1.5 isolates had cellulase enzyme activity of 132.16 and 127.3 U/mL, respectively. These isolates can grow and degrade cellulose at 30°C to 35°C and pH of 2, 3, 4, and 5.  The HS3.4.1 and HS1.5 isolate were closely related to Penicillium citrinum based on the phylogenetic tree analysis.